Adverse reaction to nicotine gum in a poor metaboliser - Robson, N.Z.; Bond, A.J.; Wolff, K. (2008)
Purpose: To report a case of adverse reaction to nicotine gum in a Chinese female with poor nicotine metabolic status after chewing a piece of 2 mg nicotine gum (NG). Background: NG is prescribed in smoking cessation programs to help individuals stop smoking. In smoking cessation treatment, the dose of NG should control withdrawal symptoms but avoid adverse effects. Case results: We describe a case of an adverse reaction following the administration of 2 mg NG to a female Chinese subject. This study compared a single dose of 2 mg NG with a single low dose cigarette (0.7 mg nicotine). Blood (5mL) was collected at baseline and 2h post exposure to NG. Blood pressure and pulse rate were also recorded. Nicotine metabolic rate was determined by calculation of the ratio of plasma cotinine (ng/mL)/plasma nicotine (ng/mL). The subject developed nausea and severe vomiting with raised blood pressure and pulse rate following administration of NG. The ratio of plasma cotinine/nicotine was 0.4 indicative of poor nicotine metabolic rate. Exposure to nicotine using the subject's normal cigarette did not produce similar adverse effects. Conclusion: NG may be associated with adverse reactions in smokers with low nicotine metabolic rate. Physicians in smoking cessation programs should be aware that some individuals may not tolerate this form of pharmacological treatment.